TRANSLATION TECHNIQUES FOR IDIOMATIC EXPRESSIONS IN SUBTITLING AND DUBBING: A STUDY ON RAYA AND THE LAST DRAGON - Lestari, Denisa Putri; Nugroho, Muhammad Aprianto Budie; Solihat, Dadang; Fadhly, Fahrus Zaman (Indonesian Journal of Learning and Instruction, 2023)
This study examines the translation equivalence and techniques used in translating idiomatic expressions in the subtitling and dubbing of the movie Raya and the Last Dragon. Using a qualitative case study approach, 72 idiomatic expressions were analyzed based on Nida & Taber’s theory of translation equivalence and Molina and Albir’s translation techniques. Results showed that 51% of subtitling and 52% of dubbing translations were equivalently translated into idiomatic expressions, while the remaining were rendered as non-idiomatic expressions due to the lack of equivalent idioms in the target language. Single translation techniques dominated, accounting for 98% in subtitling and 99% in dubbing, with established equivalence being the most frequently used technique. This highlights the translator's ability to maintain idiomatic meaning and cultural relevance. The study recommends exploring idiomatic translation strategies in diverse audiovisual media and cultural contexts to further enhance the understanding of effective translation techniques.Keywords: Translation techniques; idiomatic expressions; subtitling; dubbing; equivalence; established equivalence; audiovisual translation.